Arbitration in China: A Practical Guide [Book review] - CHIK, Warren B. (Institutional Knowledge at Singapore Management University, 2005)
The article reviews the book "Arbitration in China: A Practical Guide," Volume 2, edited by Jerome A. Cohen, Neil Kaplan, Peter Malanczuk, Daniel R. Fung and Wang Sheng Chang.